The Influence of Intellectual Capital and Environmental, Social, and Governance (ESG) Disclosure On Company Value - Triana Meinarsih; Johny Aninam; Hadiansyah Ma’sum; Olivia Tahalele; Rohani Purnamasari Dima (Sharia Journal and Education Center Publishing, 2026)
This study aims to empirically examine the influence of Intellectual Capital (IC) and Environmental, Social, and Governance (ESG) disclosure on company value within the context of the evolving global capital market in 2026. As traditional financial metrics increasingly fail to capture the full spectrum of corporate worth, non-financial drivers such as intangible assets and sustainability commitments have gained prominence. Using a quantitative approach and panel data analysis, this research investigates how efficient management of human, structural, and relational capital, combined with transparent ESG reporting, signals superior corporate quality to investors. The study utilizes the Value Added Intellectual Coefficient (VAIC™) model to measure IC and ESG scores based on global reporting standards. Preliminary findings suggest that both IC and ESG disclosure positively and significantly impact company value, as measured by Tobin’s Q. Furthermore, the abstract emphasizes that in a digital and socially conscious economy, the synergy between intellectual prowess and ethical governance serves as a critical determinant of long-term financial performance and market valuation.